Racializing Emasculation: An Intersectional Analysis of Queer Men's Evaluations of Sexual Assault. (5th October 2020) - Meyer, Doug
Abstract: This article focuses on how 60 queer men perceived emasculation in relation to their experiences of sexual assault, drawing particular attention to racial and ethnic differences. While previous scholarship has focused primarily on gender, the author of this article uses an intersectional approach to explore queer men's narratives. Results demonstrate that queer men of color with intra-racial experiences of assault typically denied feelings of emasculation, emphasizing instead other emotions that were intimately related to challenges they faced due to their social position. Most White participants with intra-racial experiences felt emasculated after the assault. Racial and ethnic differences appeared even more pronounced with interracial forms of violence, as Black queer men drew attention to racialized concerns, such as fear over being perceived as a "troublemaker" for reporting a White assailant, while White and Latino participants described feeling emasculated, in large part due to masculinizing stereotypes of Black men. The implications of this research suggest that emasculation is a racialized, as well as a gendered, process for queer men – one that does not arise automatically from simply being a man who has been sexually violated but one that springs disproportionately from whiteness and that generally involves particular racialized gender dynamics.